The effect of FTO rs9939609 polymorphism on the association between colorectal cancer and dietary fiber - Fathi, Soroor; Ahmadzadeh, Mina; Vahdat, Mahsa; Afsharfar, Maryam; Roumi, Zahra; Hassanpour Ardekanizadeh, Naeemeh; Shekari, Soheila; Poorhosseini, Seyed Mohammad; Gholamalizadeh, Maryam; Abdollahi, Sepideh; Kheyrani, Elham; Doaei, Saeid (Frontiers in Nutrition, 2022)
Background: Gene polymorphisms may explain the controversy on the association between colorectal cancer (CRC) and dietary fibers. The purpose of this study was to investigate the effect of Fat mass and obesity-associated (FTO) rs9939609 polymorphism on the association between colorectal cancer and dietary fiber. Methods: This case-control study was conducted on 160 cancer cases and 320 healthy controls in Tehran, Iran. The participants’ food intake was assessed using a semi-quantitative food frequency questionnaire (FFQ). The frequency of rs9939609 FTO polymorphism in the case and control groups was determined using the tetra-primer amplification refractory mutation (tetra-ARMS) method. Results: In the participants with the TT genotype of the FTO rs9939609, the cases had higher BMI and lower intake of dietary fiber (23.99 ± 4.42 vs. 26.41±7.63 g/d, P=0.01) compared to the controls. Among A allele carriers of FTO rs9939609 polymorphism, the cases had higher BMI (28.68±4.06 vs. 27.58 ±3.25 k/m2, P=0.04) and lower fiber intake (23.77±5.02 vs. 25.67±4.62 g/d, P=0.02) and soluble fiber (0.9 ± 0.65 vs. 1.02 ± 0.78 g/d, P= 0.02). An inverse association was found between CRC and dietary fiber intake among those with the AA/AT FTO rs9939609 genotype after adjusting for age, sex, smoking, alcohol consumption, physical activity, BMI, and calorie intake (OR=0.9, CI95%:0.84-0.92, P<0.05). Conclusions: This study found a link between higher dietary fiber consumption and a lower risk of CRC in A-allele carriers of FTO rs9939609 polymorphism. Future research should identify the underlying mechanisms of the association between CRC and dietary components in people with different FTO genotypes.